Management of paediatric dermatological emergencies. Issue 2 (February 2015) - Rashid, Rabia; Goodyear, Helen
Abstract: Most skin diseases can be safely managed in outpatients; however, in a significant proportion of cases, immediate and aggressive intervention is required. Recognition of these more serious and potentially life-threatening dermatological presentations is imperative in order to provide correct emergency treatment and limit morbidity and mortality. This article looks at conditions which may present in childhood that might require urgent treatment. These include infection, drug reactions, erythroderma, congenital ichthyoses (especially collodian baby and Harlequin ichthyosis), Stevens–Johnson syndrome, toxic epidermal necrolysis, infantile haemangiomas and epidermolysis bullosa.